2014
DOI: 10.1002/2013jb010795
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic signatures in time gravity variations during the volcanic unrest on El Hierro (Canary Islands)

Abstract: Gravity changes occurring during the initial stage of the 2011-2012 El Hierro submarine eruption are interpreted in terms of the preeruptive signatures during the episode of unrest. Continuous gravity measurements were made at two sites on the island using the relative spring gravimeter LaCoste and Romberg gPhone-054. On 15 September 2011, an observed gravity decrease of 45 μGal, associated with the southward migration of seismic epicenters, is consistent with a lateral magma migration that occurred beneath th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Another interesting feature revealed in our study is that the main earthquake was the largest and latest part of a process that started the day before (7 October 2011, 22:14 UTC). This time coincides to when López et al (2014) reports the beginning of the upward seismic hypocenter migration, the maximum release of seismic energy, and reaching the maximum strain rate of the preeruptive swarm and the first days of the eruption, and with gravity changes reported in Sainz-Maza Aparicio et al (2014). Ibáñez et al (2012) also observed a considerable decrease in b-values in that period compared to the previous weeks of the unrest.…”
Section: Discussionsupporting
confidence: 72%
“…Another interesting feature revealed in our study is that the main earthquake was the largest and latest part of a process that started the day before (7 October 2011, 22:14 UTC). This time coincides to when López et al (2014) reports the beginning of the upward seismic hypocenter migration, the maximum release of seismic energy, and reaching the maximum strain rate of the preeruptive swarm and the first days of the eruption, and with gravity changes reported in Sainz-Maza Aparicio et al (2014). Ibáñez et al (2012) also observed a considerable decrease in b-values in that period compared to the previous weeks of the unrest.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, past studies have shown that the combined effect of instrumental drift and environmental factors (mostly, ambient temperature) may induce strong apparent gravity changes that are difficult to predict since highly nonlinear, instrument‐specific, and frequency‐dependent modeling schemes are required (Andò & Carbone, ). If a suitable setup is adopted for the field stations, these effects become negligible over short intervals, which explains why most past studies at active volcanoes have focused on the analysis of continuous gravity observations over time scales of minutes to a few days (e.g., Branca et al, ; Carbone et al, , , , , ; Carbone & Poland, ; Gottsmann et al, ; Poland & Carbone, , ; Sainz‐Maza Aparicio et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…(17)). An arbitrary constant value was subtracted from the gravity values, so as to conform the maximum of the daily average gravity to 0 Here we discuss several effects of mass distributions associated with volcanism [e.g., Furuya et al, 2003;Del Negro et al, 2013;Aparicio et al, 2014], in order to explain the physical mechanism of the residual gravity observed at Asama Volcano in 2004 ( Figure 9). We also utilize the observed data other than gravity, such as the emission rate of volcanic gas, because each effect of mass distribution cannot be isolated from the observed gravity values (= the integral of all of mass distributions).…”
Section: Discussion On the Residual Gravity In 2004mentioning
confidence: 99%